Preparation method of mechanical activation lithium slag non-burning light aggregate without additional alkali activator
Patent Information
- Application Number
- CN202611028866.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-30
AI Technical Summary
(1)碱激发剂的使用增加了生产成本,且碱激发剂在生产、储存和运输过程中存在安全和环保风险;
1、本发明利用锂渣自身石膏与含钙固废协同,形成自激发水化体系,无需额外激发剂,彻底消除了泛碱风险,避免了设备腐蚀。。
Abstract
Description
Technical Field
[0001] This invention relates to a technology for the resource utilization of building materials and industrial solid waste, and in particular to a method for preparing mechanically activated lithium slag non-burning lightweight aggregate without the addition of external alkali activators. Background Technology
[0002] Lithium slag is a large-scale industrial solid waste generated during the lithium extraction process from spodumene or lepidolite. With the rapid development of new energy vehicles and energy storage industries, the demand for lithium salt products continues to grow, leading to a year-on-year increase in lithium slag emissions. The main chemical components of lepidolite leaching residue are SiO2, Al2O3, and CaO, with mass fractions of 25.63%, 18.55%, and 18.66%, respectively. The main phase composition is lapis lazuli (41%), feldspar (20%), gypsum (17%), leucite (16%), and small amounts of zeolite (5%) and fluorite (1%). The presence of amorphous silica-alumina components in lithium slag gives it potential pozzolanic activity, making it a potential auxiliary cementing material. However, the natural activity of lithium slag is low, requiring physical activation and chemical stimulation to enhance its reactivity.
[0003] Utilizing lithium slag to prepare lightweight aggregates is one of the effective ways to achieve large-scale resource utilization. In existing technologies, the preparation of non-fired lightweight aggregates from lithium slag typically requires the addition of alkaline activators. For example, patent CN117185690B discloses a lithium slag-based non-fired lightweight ceramsite, whose raw materials include 60-80 parts lithium slag, 10-20 parts cement, 8-15 parts quicklime, 3-8 parts alkaline activator, 1-6 parts foaming agent, and 12-20 parts water. Patent CN120309273A discloses a non-fired lightweight aggregate with high lithium slag content, whose raw materials include lepidolite slag and spodumene slag, as well as functional additives including activators. All of the above patents rely on the use of alkaline activators.
[0004] Furthermore, patent CN121850553A discloses a solid waste building material and its preparation method, which uses steel slag, lithium slag, carbide slag, and water as raw materials. After casting and molding, the material is prepared into block-shaped building materials through carbonization curing. This method uses steel slag as the main material (accounting for more than 55% of the total solid phase), with lithium slag content only 19%–26%, and it must rely on CO2 carbonization curing to obtain sufficient strength and stability. This patent does not involve the granulation and molding process of lightweight aggregates, nor does it involve mechanical activation technology, and its carbonization curing process is fundamentally different from the atmospheric pressure curing process of non-fired lightweight aggregates.
[0005] However, the existing technology has the following technical problems: (1) The use of alkaline activators increases production costs, and there are safety and environmental risks associated with the production, storage and transportation of alkaline activators; (2) Alkali-activated lightweight aggregate products are prone to efflorescence during use, which affects the appearance quality and long-term durability of the products; (3) Alkali activators are highly corrosive to equipment, increasing equipment maintenance costs and replacement frequency; (4) When the natural activity of lithium slag is not fully activated, the strength of the product is difficult to meet the requirements, and excessive use of alkali activator will lead to efflorescence and durability problems. (5) Existing lithium slag-based non-fired lightweight aggregates usually require the addition of a high proportion of cement or other cementing materials, which increases production costs and carbon emissions. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing mechanically activated lithium slag non-burning lightweight aggregate without the addition of an external alkali activator, which has a reasonable design, high lithium slag content, simple process and excellent product performance.
[0007] The technical solution of this invention is: A method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator includes the following steps: Step S1: Drying and pre-grinding of lithium slag. The lithium slag produced by the lithium extraction process is dried at 100-110℃ until the moisture content is less than 1%, and then pre-grinded and passed through a 100-200 mesh sieve to obtain lithium slag powder.
[0008] Step S2: Mechanical activation of lithium slag. The lithium slag powder obtained in step S1 is placed in a ball mill for mechanical activation treatment. The mechanical activation treatment uses a planetary ball mill or a vibratory ball mill. The milling media are zirconia balls or steel balls, the ball-to-material mass ratio is 8:1 to 15:1, the milling speed is 300 to 500 r / min, and the milling time is 1 to 4 hours. After mechanical activation, the specific surface area of the lithium slag powder is 800 to 2000 m² / kg, preferably 1200 to 1800 m² / kg.
[0009] Step S3: Construction of the activation system without added alkali activator. The mechanically activated lithium slag powder obtained in step S2 is mixed with industrial solid waste containing active calcium oxide at a mass ratio of (65-85):(15-35) to obtain an activated mixture without added alkali activator. The industrial solid waste containing active calcium oxide is selected from carbide slag, steel slag, or any mixture thereof in any proportion. Among them, the Ca(OH)2 content in the carbide slag is not less than 80%, and the f-CaO content in the steel slag is not less than 3%.
[0010] It should be noted that the "no added alkali activator" in this invention refers to the absence of conventional alkali metal salt chemical activators such as water glass (sodium silicate, potassium silicate), sodium hydroxide, and potassium hydroxide during the preparation process. The calcium hydroxide from industrial solid waste containing active calcium oxide (such as carbide slag) used in this invention participates in the hydration reaction as a calcium-based reactant in this system. It reacts with the active silica-alumina components released from mechanically activated lithium slag and the sulfate minerals contained in the lithium slag itself to generate hydrated calcium silicate (CSH) gel and ettringite (AFt), thereby giving the system strength. This hydration hardening mechanism is fundamentally different from the alkali-activated geopolymer mechanism that relies on strong alkali depolymerization of aluminosilicates. Therefore, the technical solution of this invention should not be categorized as "alkali-activated" technology.
[0011] Step S4: Homogenization treatment of the mixture. Add water accounting for 15% to 25% of the total mass of the mixture to the activated mixture without added alkali activator obtained in step S3. After stirring and mixing evenly, let it stand and age for 20 to 60 minutes to fully wet the material and allow it to undergo a preliminary hydration reaction, thus obtaining a homogenized wet material.
[0012] Step S5: Granulation and forming. The homogenized wet material obtained in step S4 is placed in a disc granulator for granulation and forming. The disc inclination angle of the disc granulator is 40° to 55°, and the rotation speed is 20 to 50 r / min. During the granulation process, water, accounting for 1% to 5% of the total mass of the mixture in step S4, is added by spraying according to the material state. The particle size of the raw material pellets obtained by granulation is controlled to be 5 to 20 mm, preferably 8 to 15 mm.
[0013] Step S6: Curing treatment. The raw material pellets obtained in step S5 are subjected to curing treatment. The curing treatment adopts any one or a combination of two or more of the following methods: natural curing, steam curing, or autoclaving. The curing treatment is carried out in a non-carbonizing atmosphere, i.e., without carbon dioxide carbonization curing. After curing, the mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator is obtained.
[0014] Preferably, the mass ratio of balls to material in the mechanical activation treatment in step S2 is 10:1 to 12:1, the ball milling speed is 350 to 450 r / min, and the ball milling time is 2 to 3 hours.
[0015] Preferably, in step S3, the mass ratio of mechanically activated lithium slag powder to industrial solid waste containing active calcium oxide in the activated mixture without added alkali activator is (70-80):(20-30).
[0016] Preferably, the lithium slag is any one or a mixture of two of the following: lithium mica slag or lithium spodumene slag.
[0017] Preferably, the industrial solid waste containing active calcium oxide is carbide slag, and the Ca(OH)2 content in the carbide slag is not less than 85%.
[0018] Preferably, the curing treatment adopts a combination of natural curing and steam curing: first, the raw material balls are naturally cured at 15-30℃ and relative humidity of not less than 90% for 12-36 hours, and then steam cured at 60-90℃ for 12-48 hours.
[0019] The present invention also provides a mechanically activated lithium slag non-burning lightweight aggregate prepared by the above method without added alkali activator, the aggregate ball diameter being 8-15 mm, the bulk density being 768-846 kg / m³, and the cylinder compressive strength being 5.4-7.1 MPa.
[0020] The present invention further provides the application of the mechanically activated lithium slag non-fired lightweight aggregate without added alkali activator in lightweight concrete, lightweight blocks, lightweight insulation materials, and roadbed materials.
[0021] The beneficial effects of this invention are: 1. This invention utilizes the gypsum inherent in lithium slag and the synergistic effect of calcium-containing solid waste to form a self-activated hydration system, eliminating the need for additional activators, completely removing the risk of efflorescence, and preventing equipment corrosion.
[0022] 2. This invention utilizes mechanical activation to cause lattice distortion in the crystal structure of lithium slag powder under mechanical force, generating a large number of surface defects and amorphous silicon-aluminum phases, thereby significantly improving the pozzolanic activity of lithium slag. Furthermore, the lithium slag content can reach 65% to 85%, enabling large-scale utilization.
[0023] 3. This invention achieves lightweight and high-strength products without adding foaming agents through high dosage, process control, and synergistic effect of ettringite micro-expansion. At the same time, it eliminates the need for calcination granulation and carbonization curing, resulting in a simple process, low energy consumption, and low carbon emissions.
[0024] 4. The product of this invention meets the technical requirements of GB / T 17431.1-2010, has a wide range of applications, and simultaneously disposes of two types of industrial solid waste, resulting in significant environmental and social benefits. Detailed Implementation Example 1:
[0025] Lithium-extracting slag from lepidolite was dried at 105℃ to a moisture content of 0.8% and pre-ground through a 150-mesh sieve. The lithium slag powder was placed in a planetary ball mill at a ball-to-material mass ratio of 10:1, a rotation speed of 400 r / min, and milled for 2 hours to obtain mechanically activated lithium slag powder with a specific surface area of 1560 m² / kg. 75 kg of this powder was mixed evenly with 25 kg of calcium carbide slag (Ca(OH)₂ content 88%), and 20 kg of water was added and stirred. The mixture was then aged for 30 minutes. The wet material was placed in a disc granulator at a disc inclination angle of 45° and a rotation speed of 35 r / min to granulate into 8–15 mm raw pellets. The raw pellets were first naturally cured for 24 hours at room temperature and humidity ≥90%, and then steam-cured at 80℃ for 24 hours (non-carbonizing atmosphere). Performance test results: bulk density 785 kg / m³, cylinder compressive strength 6.2 MPa, water absorption rate 8.5% in 1 hour, softening coefficient 0.88.
[0026] If necessary, add 5 kg of water by spraying during the granulation process. Example 2:
[0027] The difference from Example 1 is that the mass ratio of mechanically activated lithium slag powder to calcium carbide slag is 80:20, the ball milling time is 3 hours, the rotation speed is 350 r / min, and the specific surface area is 1820 m² / kg. Performance test results: bulk density 812 kg / m³, cylinder compressive strength 5.8 MPa, 1-hour water absorption rate 9.2%, and softening coefficient 0.85. Example 3:
[0028] The difference from Example 1 is that the calcium-containing solid waste used is steel slag (f-CaO content 4.2%), with a mass ratio of 70:30. Performance test results: bulk density 846 kg / m³, cylinder compressive strength 5.4 MPa, 1h water absorption rate 10.1%, softening coefficient 0.82. Example 4:
[0029] The difference from Example 1 is that autoclaving is used: the raw material balls obtained in step S5 are placed in an autoclave and cured for 8 hours at 150°C and 0.5 MPa in a non-carbonizing atmosphere. Other steps are the same as in Example 1. Performance test results: bulk density: 768 kg / m³, cylinder compressive strength: 7.1 MPa, 1-hour water absorption rate: 7.8%, softening coefficient: 0.91. Example 5:
[0030] The difference from Example 1 is that 1.5% bentonite plasticizer was added, the ball-to-material mass ratio was 12:1, the rotation speed was 450 r / min, the time was 1.5 hours, and the specific surface area was 1350 m² / kg. Performance test results: bulk density 792 kg / m³, cylinder compressive strength 6.5 MPa, 1-hour water absorption rate 8.0%, and softening coefficient 0.89.
[0031] Comparative Example 1: No mechanical activation was performed (only pre-grinding through a 150-mesh sieve), otherwise the same as in Example 1. Performance: bulk density 892 kg / m³, cylinder compressive strength 3.2 MPa, 1-hour water absorption rate 14.5%, softening coefficient 0.65.
[0032] Comparative Example 2: No carbide slag is added; only 100% mechanically activated lithium slag powder is used. Performance: Bulk density 756 kg / m³, compressive strength 2.1 MPa, 1-hour water absorption rate 18.3%, softening coefficient 0.48.
[0033] Comparative Example 3: Referring to the proportions in Example 1 of CN121850553A: 1200g steel slag, 500g lithium slag, 100g calcium carbide slag, and 300g water, granulated according to the process of this invention and cured naturally with steam (without carbonization). Performance: bulk density 928kg / m³, compressive strength 2.8MPa, 1h water absorption rate 16.2%, softening coefficient 0.55.
[0034] The data shows that mechanical activation and calcium carbide slag (or steel slag) are crucial for forming a self-activating system without added alkali activators. The raw material ratio and process of this invention are synergistic and irreplaceable.
[0035] It should be noted that this invention utilizes the gypsum (CaSO4·2H2O) contained in lithium slag as the core functional component, which reacts synergistically with Ca(OH)2 provided by carbide slag and active Al2O3 released by mechanical activation to generate stable ettringite and hydrated calcium silicate gel. During this reaction, a large amount of sulfate in the lithium slag is consumed and converted into ettringite crystals with extremely low solubility, preventing the release of sulfate ions during subsequent use. Therefore, although the raw material has a high sulfate content, the soluble sulfate content in the finished lightweight aggregate is significantly reduced after sufficient hydration. Simultaneously, the finished lightweight aggregate meets the relevant technical requirements of GB / T 17431.1-2010 "Lightweight Aggregates and Their Test Methods" regarding mud content, mud lump content, boiling loss, loss on ignition, organic matter content, chloride content, and radioactivity.
[0036] The scientific mechanism by which this invention achieves lightweighting lies in the following: First, by using high-content lithium slag (65%–85%) without adding cement, the low bulk density of lithium slag (generally 700–900 kg / m³, which can be further reduced after mechanical activation and grinding) is utilized, thus reducing the solid-phase density at the source. Second, during the granulation process, by controlling the moisture content (15%–25%) and the parameters of the disc granulation process, a certain amount of air micropores are encapsulated inside the raw material pellets, forming a loose structure. Third, the active Al₂O₃ released by the mechanically activated lithium slag, together with the Ca(OH)₂ provided by the carbide slag and the gypsum (CaSO₄·2H₂O) contained in the lithium slag itself, generates a large number of needle-like ettringite (AFt) crystals during hydration. The formation of ettringite is accompanied by a solid-phase volume expansion of approximately 120%–130%, which effectively expands the hardened slurry structure, forming an interwoven porous network skeleton, thereby achieving lightweighting without foaming agents or sintering.
[0037] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications made based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator, comprising the following steps: Step S1: Dry the lithium slag to a moisture content of less than 1%, pre-grind it, and then pass it through a 100-200 mesh sieve to obtain lithium slag powder; Step S2: The lithium slag powder obtained in step S1 is subjected to mechanical activation treatment. The mechanical activation is carried out by ball milling, with a ball-to-material mass ratio of 8:1 to 15:1, a ball milling speed of 300 to 500 r / min, and a ball milling time of 1 to 4 hours, to obtain mechanically activated lithium slag powder with a specific surface area of 800 to 2000 m² / kg. Step S3: Mix the mechanically activated lithium slag powder obtained in step S2 with industrial solid waste containing activated calcium oxide at a mass ratio of (65-85):(15-35) to obtain an activated mixture without added alkali activator. Step S4: Add water accounting for 15% to 25% of the total mass of the mixture to the activated mixture without added alkali activator obtained in step S3, stir and mix evenly, and let it stand for aging for 20 to 60 minutes to fully wet the material and allow it to undergo a preliminary hydration reaction to obtain a homogenized wet material. Step S5: The homogenized wet material obtained in step S4 is granulated to obtain raw material balls with a particle size of 5-20 mm; Step S6: The raw material pellets obtained in step S5 are cured in a non-carbonizing atmosphere. After curing, mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator is obtained.
2. The method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator according to claim 1, characterized in that: In step S2, the mass ratio of ball to material in the mechanical activation treatment is 10:1 to 12:1, the ball milling speed is 350 to 450 r / min, the ball milling time is 2 to 3 hours, and the specific surface area of the lithium slag powder after mechanical activation is 1200 to 1800 m² / kg.
3. The method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator according to claim 1, characterized in that: In step S3, the industrial solid waste containing active calcium oxide is carbide slag, and the Ca(OH)2 content in the carbide slag is not less than 80%; the mass ratio of mechanically activated lithium slag powder to industrial solid waste containing active calcium oxide in the activated mixture without added alkali activator is (70-80):(20-30).
4. The method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator according to claim 1, characterized in that: In step S1, the lithium slag is any one or a mixture of two of the following: lithium mica lithium extraction slag or lithium spodumene lithium extraction slag.
5. The method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator according to claim 1, characterized in that: The aging time in step S4 is 30 to 45 minutes.
6. The method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator according to claim 1, characterized in that: The granulation process described in step S5 uses a disc granulator with a disc inclination angle of 40° to 55° and a rotation speed of 20 to 50 r / min. During the granulation process, water accounting for 1% to 5% of the total mass of the mixture in step S4 is added by spraying. The resulting raw material pellets have a particle size of 8 to 15 mm.
7. The method for preparing mechanically activated lithium slag non-fired lightweight aggregate without added alkali activator according to claim 1, characterized in that: The curing treatment described in step S6 adopts a combination of natural curing and steam curing: first, the raw material balls are naturally cured for 12 to 36 hours at 15 to 30°C and relative humidity not less than 90%, and then steam cured for 12 to 48 hours at 60 to 90°C.
8. The method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator according to claim 1, characterized in that: The curing treatment described in step S6 adopts the autoclaving method: the raw material pellets are cured in an autoclave at 120-180℃ and 0.2-1.0MPa for 4-12 hours.
9. The method for preparing mechanically activated lithium slag non-burning lightweight aggregate without added alkali activator according to claim 1, characterized in that: In step S3, the activated mixture without added alkali activator is further enhanced with a plasticizer comprising 0.5% to 3% of the total mass of the mixture. The plasticizer is selected from any one or a mixture of two or more of bentonite, diatomite, or attapulgite.
10. A mechanically activated lithium slag non-fired lightweight aggregate without added alkali activator, characterized in that: The pellets have a diameter of 8–15 mm, a bulk density of 768–846 kg / m³, and a compressive strength of 5.4–7.1 MPa. They are prepared by the preparation method described in any one of claims 1–9 and are used in lightweight concrete, lightweight blocks, lightweight insulation materials, and roadbed materials.
Citation Information
Patent Citations
Lithium slag-based unfired light ceramsite and its preparation method and application
CN117185690B
Unfired lightweight aggregate with high lithium slag doping amount and method for synergistically preparing unfired lightweight aggregate from lepidolite slag and lepidolite slag
CN120309273A
All-solid waste building material and preparation method thereof
CN121850553A